The availability and diversity of food items sold in spaza shops around the Moletši area in the Limpopo Province : a cross-sectional study - Setati, Matlou Bartina (Stellenbosch : Stellenbosch University, 2022)
Thesis (MSc)--Stellenbosch University, 2022.